Clonal Variation in Casuarina junghuhniana and its Hybrids for Vegetative Propagation as Influenced by Propagule Size - Sra, Manpreet Singh; Garg, Rakesh Kumar (Indian Forester, 2022)
This study aimed to evaluate the effect of different cutting sizes on performance of different clones for rooting ability and other morphological parameters for vegetation propagation of Casuarina clones under controlled climatic conditions. Six clones of Casuarina viz. IFGTB CH1, IFGTB CH 2, IFGTB CH 4 IFGTB CH 5, IFGTB CH 6 and IFGTB CJ 7 were selected for the present study. Three cutting sizes i.e. diameter of <0.3cm, 0.3-0.6cm and 0.6- 0.9cm were tested to see the effect on propagation. Clone IFGTB CH 4 registered its superiority for sprouting (69.61%), survival (37.75%) and days taken for sprouting (3.00 days). Clone IFGTB CH 5 performed better for shoot and root parameters. Cutting diameter of <0.3cm resulted in highest survival (40.01%), plant height (46.63 cm), number of days taken for sprouting initiation (4.66 days) and branches number (1.41). High genotypic coefficient of variation, phenotypic coefficient of variation, heritability and genetic gain were recorded for most of the traits. Highest phenotypic correlation was observed between root dry weight and root fresh (0.9219). Highest direct effect on root dry weight was recorded by root fresh weight (0.2828) and indirect effect was registered by root length through collar diameter (0.2486).